Pharmacological modulation of responses of guinea-pig airways contracted with antigen and calcium ionophore A23187. - Burka, J. F. (1985)
Ovalbumin (OA) and calcium ionophore A23187 were used to induce contractions of sensitized guinea-pig tracheal and lung parenchymal preparations in the presence and absence of indomethacin. This model was used to examine the properties of a series of compounds reported to inhibit 5-lipoxygenase or to antagonize lipoxygenase products at the receptor level. FPL55712 and piriprost appeared to act as pharmacological antagonists because they rapidly reduced tracheal tone established by OA. The prolonged phase (i.e. greater than 10 min post-challenge) of airways contractions induced by OA is assumed to be lipoxygenase-dependent and was inhibited by nordihydroguaiaretic acid (NDGA), FPL55712, nafazatrom and benoxaprofen, in order of potency. Piriprost had similar inhibitory effects on the trachea, but not on lung parenchyma. The inhibitory effects of NDGA and FPL55712 were reduced, and those of nafazatrom increased by indomethacin. Indomethacin decreased the inhibitory effect of piriprost on the trachea, but facilitated inhibition by this agent on the parenchyma. A roughly similar pattern was seen on A23187-induced contractions, but FPL55712 did not modify these contractions and benoxaprofen enhanced the response of the trachea. BW755C enhanced the overall contractile response of OA- and A23187-induced tracheal contractions (but not parenchymal contractions) in a bell-shaped manner, an effect not seen in the presence of indomethacin. This indicated that BW755C could be acting as a cyclo-oxygenase inhibitor. The results suggested that, although inhibitors of the lipoxygenase pathway were partially effective in inhibiting the contractions of the airways induced by OA or A23187, other mediators in addition to those of the lipoxygenase pathway contribute to these contractions.